Self-Control as Conceptual Framework to Understand and Support People Who Use Drugs During Sex - Platteau, Tom; Florence, Eric; de Wit, John B. F. (Frontiers in Public Health, 2022)
Few theory-informed interventions to support people who use drugs during sex have been conceptualized and developed. We conceptualize sexualized drug use, also referred to as chemsex or pharmacosex, as a self-control challenge, and draw on extant theory and research to propose intervention approaches that can be tailored to meet the differing needs of people who engage in sexualized drug use. We draw on a continuum perspective of sexualized drug use, in particular chemsex, and discuss the role of reasoned and automatic processes in behavioral decisions, as well as critical components of effective self-control of behavior. A self-control approach can empower people to tackle their sexualized drug use, and classify their experienced sex-related drug use as problematic. Self-control encompasses clarifying one's goals and identifying strategies to mitigate behaviors to achieve these goals, despite competing pharmacosex desires. Our approach to self-control sexualized drug use contains three critical components: goal setting, goal enactment, and goal progress appraisal and goal adjustment. Goals should be formulated specific, ambitious yet realistic, and tailored to the individual's needs and wishes. Goals may target aspects of drug use, protecting sexual health and mitigating negative impacts. Implementing goal enactment implies translating goals into concrete (short-term) actions to move toward the higher-order goal via goal intentions and action/coping plans. During the goal progress appraisal and adjustment stage, people compare their actual with their planned behavior. This reflection may result in goal adjustment through feedback loops to adjust their goals and action/coping plans. We propose that our self-control approach can guide the development of interventions to effectively support people to prevent or limit pharmacosex, and helps to effectively mitigate or reduce negative impacts via self-help, peer support or professional support, offered via personal counseling or digital tools.